Respuesta :
[tex]\bf 2[x^2+y^2]^2=25(x^2-y^2)\qquad \qquad
\begin{array}{lllll}
&x_1&y_1\\
% (a,b)
&({{ 3}}\quad ,&{{ 1}})\quad
\end{array}\\\\
-----------------------------\\\\
2\left[ x^4+2x^2y^2+y^4 \right]=25(x^2-y^2)\qquad thus
\\\\\\
2\left[ 4x^3+2\left[ 2xy^2+x^22y\frac{dy}{dx} \right]+4y^3\frac{dy}{dx} \right]=25\left[2x-2y\frac{dy}{dx} \right]
\\\\\\
2\left[ 4x^3+2\left[ 2xy^2+x^22y\frac{dy}{dx} \right]+4y^3\frac{dy}{dx} \right]=50\left[x-y\frac{dy}{dx} \right]
\\\\\\
[/tex]
[tex]\bf \left[ 4x^3+2\left[ 2xy^2+x^22y\frac{dy}{dx} \right]+4y^3\frac{dy}{dx} \right]=25\left[x-y\frac{dy}{dx} \right] \\\\\\ 4x^3+4xy^2+4x^2y\frac{dy}{dx}+4y^3\frac{dy}{dx}+25y\frac{dy}{dx}=25x \\\\\\ \cfrac{dy}{dx}[4x^2y+4y^3+25y]=25x-4x^3+4xy^2 \\\\\\ \cfrac{dy}{dx}=\cfrac{25x-4x^3+4xy^2}{4x^2y+4y^3+25y}\impliedby m=slope[/tex]
notice... a derivative is just the function for the slope
now, you're given the point 3,1, namely x = 3 and y = 1
to find the "m" or slope, use that derivative, namely [tex]f'(3,1)=\cfrac{25x-4x^3+4xy^2}{4x^2y+4y^3+25y}[/tex]
that'd give you a value for the slope
to get the tangent line at that point, simply plug in the provided values
in the point-slope form
[tex]\bf y-{{ y_1}}={{ m}}(x-{{ x_1}})\qquad \begin{cases} x_1=3\\ y_1=1\\ m=slope \end{cases}\\ \qquad \uparrow\\ \textit{point-slope form}[/tex]
and then you solve it for "y", I gather you don't have to, but that'd be the equation of the tangent line at 3,1
[tex]\bf \left[ 4x^3+2\left[ 2xy^2+x^22y\frac{dy}{dx} \right]+4y^3\frac{dy}{dx} \right]=25\left[x-y\frac{dy}{dx} \right] \\\\\\ 4x^3+4xy^2+4x^2y\frac{dy}{dx}+4y^3\frac{dy}{dx}+25y\frac{dy}{dx}=25x \\\\\\ \cfrac{dy}{dx}[4x^2y+4y^3+25y]=25x-4x^3+4xy^2 \\\\\\ \cfrac{dy}{dx}=\cfrac{25x-4x^3+4xy^2}{4x^2y+4y^3+25y}\impliedby m=slope[/tex]
notice... a derivative is just the function for the slope
now, you're given the point 3,1, namely x = 3 and y = 1
to find the "m" or slope, use that derivative, namely [tex]f'(3,1)=\cfrac{25x-4x^3+4xy^2}{4x^2y+4y^3+25y}[/tex]
that'd give you a value for the slope
to get the tangent line at that point, simply plug in the provided values
in the point-slope form
[tex]\bf y-{{ y_1}}={{ m}}(x-{{ x_1}})\qquad \begin{cases} x_1=3\\ y_1=1\\ m=slope \end{cases}\\ \qquad \uparrow\\ \textit{point-slope form}[/tex]
and then you solve it for "y", I gather you don't have to, but that'd be the equation of the tangent line at 3,1